Preferensi dan Tingkat Serangan Keong Mas (Pomaceae canaliculata Lamarck) terhadap Beberapa Varietas Padi (Oryza sativa Linnaeus): english - Rusli, Rusdi; Gani, Suardi; Hutasoit, Rudy Thomson (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2018)
The study of preference dan attack level of golden apple snail (Pomaceae canaliculata Lamarck) on several rice varieties was carried out in farmers' paddy fields at Limau Manis, Pauh District, Padang, West Sumatera. The aim of this study was to obtain golden apple snail preferences and its attack level on several rice varieties. The experiments used a Randomized Block Design (RBD) with 8 treatments and 3 blocks. The treatments were several varieties commonly grown in West Sumatera, namely: Cisokan, IR 42, Anak Daro, IR 66, Batang Piaman, Ceredek Merah, Kuriek Kusuik, and Junjuang. The parameters observed were the preference, percentage and intensity of golden apple snail attacks on rice, and rice yield. The results showed that golden apple snail liked all rice varieties, but different varieties affected the preference and attack level. The three most preferred rice varieties by golden apple snail were IR 66, IR 42 and Anak Daro. Meanwhile the three least preferred rice varieties were Kuriek Kusuik, Batang Piaman and Junjuang with a low attack level and a high of yield.